From Bones to Sacred Artefact - Arponen, Aki Voitto (Temenos, 2018)
The cult of saints and the subsequent interest in relics constituted one of the essential characteristics of medieval Western Christianity. In particular, relics and reliquaries are prime examples of the importance of materiality in devotion. In the present article we analyse one of the medieval skull relics of Turku Cathedral and its material characteristics in detail. Previous examinations undertaken in the 1920s and 1940s produced two theories of its origins and identification. By analysing the bone material and the narrative depiction of martyrdom embroidered on the silk wrapping, State Archaeologist Juhani Rinne connected the relic to St Henry, the patron saint of Finland and the cathedral, while State Archaeologist Carl Axel Nordman identified it as belonging to St Eric, the patron saint of the Kingdom of Sweden. By re-examining the central element of the skull relic, the bones, with osteological analysis and radiocarbon dating, we show both theories to be highly problematic. Our analysis reveals the complex material features of the skull relic and the medieval cult of relics.